2012
DOI: 10.1074/mcp.o111.013698
|View full text |Cite
|
Sign up to set email alerts
|

Ultra High Resolution Linear Ion Trap Orbitrap Mass Spectrometer (Orbitrap Elite) Facilitates Top Down LC MS/MS and Versatile Peptide Fragmentation Modes

Abstract: Although only a few years old, the combination of a linear ion trap with an Orbitrap analyzer has become one of the standard mass spectrometers to characterize proteins and proteomes. Here we describe a novel version of this instrument family, the Orbitrap Elite, which is improved in three main areas. The ion transfer optics has an ion path that blocks the line of sight to achieve more robust operation. The tandem MS acquisition speed of the dual cell linear ion trap now exceeds 12 Hz. Most importantly, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
301
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(310 citation statements)
references
References 38 publications
4
301
2
3
Order By: Relevance
“…To the best of our knowledge, it is the first time that this has been successfully demonstrated on MALDI IMS samples. The top-down analysis has been greatly aided by the short list of proteins identified from the tissues and assembled in the subsetDB and by employing a very high performance mass spectrometer (36).This subsetDB is 4ϫ smaller than Swissprot and 15ϫ smaller than the original human IPI database commonly used in proteomics (37) and thus vastly reduces the number of proteins that have to be considered in a database search and increases the confidence in peptide identification scores. Because no protease can be specified in the search, the very high mass accuracy afforded by the mass spectrometer (single digit ppm) for intact peptides as well as fragment ions together with the small sequence database enables searching the data in a reasonable time and reduces the number of possible false positive identifications (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, it is the first time that this has been successfully demonstrated on MALDI IMS samples. The top-down analysis has been greatly aided by the short list of proteins identified from the tissues and assembled in the subsetDB and by employing a very high performance mass spectrometer (36).This subsetDB is 4ϫ smaller than Swissprot and 15ϫ smaller than the original human IPI database commonly used in proteomics (37) and thus vastly reduces the number of proteins that have to be considered in a database search and increases the confidence in peptide identification scores. Because no protease can be specified in the search, the very high mass accuracy afforded by the mass spectrometer (single digit ppm) for intact peptides as well as fragment ions together with the small sequence database enables searching the data in a reasonable time and reduces the number of possible false positive identifications (38).…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the performance of mass spectrometers is now making this more readily possible (36) and the short-list of MALDI IMS proteins generated in this study is of tremendous help for this purpose. As a proof-of-concept, we prepared MALDI matrix extracts from esophagus and colon tissue sections, mixed the extracts and analyzed these by LC-MS/MS on a high field Orbitrap mass spectrometer (36). Tandem mass spectra were charge deconvoluted and deisotoped before searching against a collection of ϳ5,500 protein sequences assembled from protein identifications made in MALDI IMS studies including the ones presented above (subsetDB, supplemental Files S1 and S2).…”
Section: A Near Complete List Of Published Maldi Ims Biomarkers-mentioning
confidence: 99%
“…Experiments were performed on an Orbitrap Elite instrument (Thermo Fisher Scientific, Waltham, MA) that was coupled to an EASY-nLC 1000 liquid chromatography (LC) system (56). The LC was operated in the two-column mode.…”
Section: Liquid Chromatography-ms/msmentioning
confidence: 99%
“…Michalski et al reported a compact high-field orbitrap, coupled with an improved Velos PRO dual ion trap mass spectrometer and advanced signal processing, capable of a nearly 4-fold increase in resolution [87]. Top-down proteomic analysis of H1299 human cancer cell line proteome using this instrument has also been reported and identified 690 unique proteins from the H1299 human cancer cell line [88].…”
Section: Orbitrap Mass Spectrometrymentioning
confidence: 99%